Incorporating lean concepts into supply chain management. (26th August 2010) - Cudney, Elizabeth; Elrod, Cassandra
Lean techniques have been implemented in a variety of industries. This paper addresses the effectiveness of specific lean techniques in a variety of industries and their application in the supply chain. The objective of this research is to assess the performance of lean based on the specific techniques and implementation methods used; analyse strategies for implementing lean into the supply chain; and to analyse the reasons for both their success and failure. Data was gathered using a survey distributed to individuals familiar with lean concepts and techniques. The results of this survey were analysed with a variety of statistical techniques.